Genomic signatures of climate adaptation in bank voles - Folkertsma, Remco; Charbonnel, Nathalie; Henttonen, Heikki; Heroldová, Marta; Huitu, Otso; Kotlík, Petr; Manzo, Emiliano; Paijmans, Johanna L. A.; Plantard, Olivier; Sándor, Attila D.; Hofreiter, Michael; Eccard, Jana A. (Ecology and evolution, 2024)
Evidence for divergent selection and adaptive variation across the landscape can provide insight into a species' ability to adapt to different environments. However, despite recent advances in genomics, it remains difficult to detect the footprints of climate‐mediated selection in natural populations. Here, we analysed ddRAD sequencing data (21,892 SNPs) in conjunction with geographic climate variation to search for signatures of adaptive differentiation in twelve populations of the bank vole (Clethrionomys glareolus) distributed across Europe. To identify the loci subject to selection associated with climate variation, we applied multiple genotype‐environment association methods, two univariate and one multivariate, and controlled for the effect of population structure. In total, we identified 213 candidate loci for adaptation, 74 of which were located within genes. In particular, we identified signatures of selection in candidate genes with functions related to lipid metabolism and the immune system. Using the results of redundancy analysis, we demonstrated that population history and climate have joint effects on the genetic variation in the pan‐European metapopulation. Furthermore, by examining only candidate loci, we found that annual mean temperature is an important factor shaping adaptive genetic variation in the bank vole. By combining landscape genomic approaches, our study sheds light on genome‐wide adaptive differentiation and the spatial distribution of variants underlying adaptive variation influenced by local climate in bank voles. We investigated adaptive differences in 12 bank vole populations across Europe in conjunction with geographic climate variation. We used multiple genotype‐environment associations, found that mean annual temperature was a shaping factor, and identified signatures of selection in candidate genes related to lipid metabolism and the immune system. Local climate is thus influencing adaptive variation in mammals.